2015
DOI: 10.1002/hbm.23020
|View full text |Cite
|
Sign up to set email alerts
|

Seeing biological actions in 3 D : An f MRI study

Abstract: Precise kinematics or body configuration cannot be recovered from visual input without disparity information. Yet, no imaging study has investigated the role of disparity on action observation. Here, we investigated the interaction between disparity and the main cues of biological motion, kinematics and configuration, in two fMRI experiments. Stimuli were presented as point‐light figures, depicting complex action sequences lasting 21 s. We hypothesized that interactions could occur at any of the three levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 75 publications
(166 reference statements)
3
16
1
Order By: Relevance
“…As expected, the main cluster involved during action observation spans across the occipital and temporal lobes, reaching the left inferior and superior temporal gyri, the fusiform gyrus and the insula. The occipito-temporal regions and the fusiform gyrus are thought to be involved in processing biological motion, of both conspecifics and nonconspecifics (Buccino et al, 2004;Georgescu et al, 2014;Jastorff et al, 2016). Consistently with the proposal of an action observation network (Grafton, 2009), we also found an involvement of the bilateral premotor cortex, BA9 and right-hemispheric convergence across BA44 and BA46.…”
Section: Action Observationsupporting
confidence: 89%
“…As expected, the main cluster involved during action observation spans across the occipital and temporal lobes, reaching the left inferior and superior temporal gyri, the fusiform gyrus and the insula. The occipito-temporal regions and the fusiform gyrus are thought to be involved in processing biological motion, of both conspecifics and nonconspecifics (Buccino et al, 2004;Georgescu et al, 2014;Jastorff et al, 2016). Consistently with the proposal of an action observation network (Grafton, 2009), we also found an involvement of the bilateral premotor cortex, BA9 and right-hemispheric convergence across BA44 and BA46.…”
Section: Action Observationsupporting
confidence: 89%
“…S1). However, others have argued that this region is found more anteriorly and in the depth of the junction between the dorsal precentral gyrus and superior frontal sulcus (Jastorff et al, 2016). Our cluster was found on the bank of the dorsal precentral gyrus near the putative boundary between dorsal and ventral PM (Tomassini et al, 2007), since it is slightly more dorsal it has been defined as the ventral part of PMd (Avanzini et al, 2016;Avanzini et al, 2018;Fan et al, 2016;Tomassini et al, 2007), and therefore labelled Area 6d/FEF.…”
Section: Premotor Regions Of the Frontal Cortexmentioning
confidence: 61%
“…In area 6d/FEF, there was a tendency for a facilitatory effect at rest, which switched to inhibition during prep-ABD, these effects were only shown in a small number of vertices, whereas a larger cluster of vertices showed a switch back to facilitation during prep-PG. We argue this cluster occupies the ventral part of PMd (Avanzini et al, 2016;Avanzini et al, 2018;Fan et al, 2016;Tomassini et al, 2007) and not FEF (Jastorff et al, 2016), especially since there is no evidence of connections between FEF and M1 (Huerta et al, 1987;Dum and Strick, 2002). Thus, differential interactions between this region and cM1 from rest to preparing to move might seem less surprising since PMd is involved in the preparation of upper limb movement (Ariani et al, 2015;Baumer et al, 2006;Begliomini et al, 2007;Begliomini et al, 2014;Gallivan et al, 2011;Rizzolatti et al, 2014).…”
Section: Premotor Regionsmentioning
confidence: 75%
“…The functional magnetic resonance imaging (fMRI) technique can be used to characterize the population‐level disparity responses. Several fMRI studies investigated population‐level disparity responses in the human cortex and revealed that V1, V2, V3, V3A, V3B, V7, hMT+/V5 (human motion complex), hV4 (human area V4), lateral occipital cortex, parietal cortex, and premotor cortex were selective for binocular disparities (Backus, Fleet, Parker, & Heeger, ; Brouwer, Van Ee, & Schwarzbach, ; Georgieva, Peeters, Kolster, Todd, & Orban, ; Gilaie‐Dotan, Ullman, Kushnir, & Malach, ; Jastorff, Abdollahi, Fasano, & Orban, ; Li et al, ; Minini, Parker, & Bridge, ; Neri, Bridge, & Heeger, ; Tsao et al, ; Welchman, Deubelius, Conrad, Bülthoff, & Kourtzi, ). Moreover, some studies applied multivoxel pattern analysis (MVPA) methods to explore the neural mechanisms that discriminate disparity levels and found that dorsal areas and posterior parietal areas had a higher predictive accuracy for decoding the disparity magnitude or depth sign than ventral areas (Patten & Welchman, ; Preston, Li, Kourtzi, & Welchman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several fMRI studies investigated population-level disparity responses in the human cortex and revealed that V1, V2, V3, V3A, V3B, V7, hMT+/V5 (human motion complex), hV4 (human area V4), lateral occipital cortex, parietal cortex, and premotor cortex were selective for binocular disparities (Backus, Fleet, Parker, & Heeger, 2001;Brouwer, Van Ee, & Schwarzbach, 2005;Georgieva, Peeters, Kolster, Todd, & Orban, 2009;Gilaie-Dotan, Ullman, Kushnir, & Malach, 2002;Jastorff, Abdollahi, Fasano, & Orban, 2016;Li et al, 2017;Minini, Parker, & Bridge, 2010;Neri, Bridge, & Heeger, 2004;Tsao et al, 2003;Welchman, Deubelius, Conrad, Bülthoff, & Kourtzi, 2005).…”
Section: Introductionmentioning
confidence: 99%